187 INGESTIONS RESULTING IN PEDIATRIC INTENSIVE CARE UNIT ADMISSION. Issue 1 (1st January 2007) - White, M. L.; Benner, K. W.; Stubbs, H. E.; Tofil, N. M.
Abstract : Introduction: Ingestions are common in pediatrics. Those that result in admission to an intensive care unit indicate significant morbidity. Characterization of these patients will allow for targeted educational and prevention efforts. Methods: We performed a retrospective chart review of patients admitted to the Children's Hospital of Alabama's pediatric intensive care unit (PICU) from 2001 to 2005 based on ICD-9 diagnostic codes. Demographic data including age, sex, race, weight, and length of PICU stay were recorded. Other data collected included drug(s) ingested, urine drug screen (UDS) and thin-layer chromatograph (TLC) results, overdose reason (accidental or intentional), outcome, need for mechanical ventilation, antidotes, and therapy received (fluid bolus, charcoal, and/or gastric lavage). Results: 160 patients were identified based on study inclusion criteria, and all charts were reviewed for data abstraction. The survival rate was 100%. The data were analyzed for patients overall and divided into groups of intentional and accidental. The overall median range for age was 4 years (range 0.42-17 years). The median length of stay was 19 hours. Forty-nine percent of the sample were male. Approximately one-third of the patients had a positive UDS, one-third had a negative UDS, and one-third did not have one performed. Therapy provided included activated charcoal (21%), gastric lavage (9%), both charcoal and lavage (22%), fluid boluses (42%), intubation (34%), and vasopressors (6%). The most frequently used antidote was Narcan, used in 48 patients. Other antidotes included glucagons, flumazenil, Mucomyst, and seizure medications. Overdoses of clonidine were the most common, occurring in 23% of our patients. Other common ingestions included polypharmacy, household products, seizure medications, tricyclic antidepressants, Tylenol, alcohols, and illegal substances. Intentional ingestions resulted in statistically significant differences by age, sex, and race. Discussion: This study characterizes severe ingestions at one pediatric institution. Additionally, it provides an opportunity to describe two main populations of patients who had severe, systemic effects from ingestions. Conclusions: Overall, survival after admission to the PICU is favorable. However, opportunities for education in the accidental ingestion and early recognition of suicidal behavior likely exist to decrease intensive care unit morbidity.